Pengaruh Likuiditas Dan Cash Flow Operation Terhadap Nilai Perusahaan serta dampaknya Terhadap Ketepatan Prediksi Saham - Riris Rotua Sitorus; Donny Syahputra (Jurnal Akuntansi Manajerial, 2023)
The impact of liquidity and cash flow operations on firm value and on the accuracy of stock predictions is the goal of this research. This study also examines the impact of liquidity and cash flow operations on the accuracy of stock predictions through firm value. The research sample consisted of 40 companies listed on the Indonesia Stock Exchange in 2019-2021 in the food and beverage and information technology sectors. The research model was tested by path analysis, using Stata software to test the direct and indirect effects. The results of the study prove that liquidity has a positive and significant effect on firm value. Cash flow operations have no effect and are negative on company value. The accuracy of stock predictions has a positive and significant effect on firm value. Liquidity has a positive and significant effect on the accuracy of stock predictions. Cash flow operations have no positive effect on the accuracy of stock predictions. Firm value is able to mediate a positive and significant relationship between liquidity and the accuracy of stock predictions. Firm value is not able to mediate and there is a negative relationship between cash flow operations and the accuracy of stock predictions.